Los inicios de la moneda dinástica en el Imperio Bizantino. La Casa de Justino y los Heráclidas - Francisco Olmos, José María de (Documenta & Instrumenta - Documenta et Instrumenta, 2009)
In this item we will go through the question of throne succession in the Byzantine Empire during the 6th and 7th centuries, and how the emperors of Justin’s House tried to impose a dynastic succession in an Empire that theoretically was ruled by the Divine Providence, of which coins were a mean of manifestation. The coin, as official document, showed the regulated succession by means of the election of a coemperor, who was not simply the designed heir, but that through his appearance in the coins was shown as the guaranty of a peaceful succession to the throne after the death of the senior Emperor. The Heraclids took a step forward in the achievement of a familiar government, and in their coins not only the designed heir is shown, but also other members of the imperial family, as well coemperors as cesars.
Keywords: Byzance; Succession to the throne; House of Justin; Heraclids; VI-VIIth Century; Dinastic coins